Ensemble empirical mode decomposition‐based differential protection scheme for islanded and grid‐tied AC microgrid. Issue 26 (17th February 2021) - Anand, Abhisekh; Affijulla, Shaik
Abstract : This study presents a differential protection scheme based on ensemble empirical mode decomposition (EEMD) for AC microgrid. The fault current level is significantly lower during the islanded operation of a microgrid, which leads to the malfunction of the traditional over‐current protection scheme. The proposed differential protection scheme uses the spectral differential energy of the first intrinsic mode function extracted from the decomposition of the current signal using EEMD for effective fault detection in the AC microgrid. The proposed EEMD‐based differential protection scheme is validated on 10 bus and modified IEEE 34‐bus AC microgrid test systems during various shunt faults. Moreover, the performance of the proposed EEMD‐based differential protection scheme is evaluated under high fault impedance scenarios. The simulation results reveal that the proposed differential protection scheme can effectively detect the faulty line in an AC microgrid during seamless islanded and grid‐tied operations.